Spark plasma sintering of ceramic matrix composite based on alumina, reinforced by carbon nanotubes; IOP Conference Series: Materials Science and Engineering; Vol. 286 : Modern Technologies and Materials of New Generations (MTMNG-2017) - Leonov A. A. Andrey Andreevich; Khasanov A. O. Aleksey Olegovich; Danchenko V. A.; Khasanov O. L. Oleg Leonidovich (2018, 2018)
Title screen